Metal oxides in heterogeneous catalysis - Vedrine, Jacques C. (Metal oxide series., 2018)
Metal Oxides in Heterogeneous Catalysis is an overview of the past, present and future of heterogeneous catalysis using metal oxides catalysts. The book presents the historical, theoretical, and practical aspects of metal oxide-based heterogeneous catalysis. Metal Oxides in Heterogeneous Catalysis deals with fundamental information on heterogeneous catalysis, including reaction mechanisms and kinetics approaches. There is also a focusiAon the classification of metal oxides used as catalysts, preparation methods and touches on zeolites, mesoporous materials and Metal-organic frameworks (MOFs) in catalysis. It will touch on acid or base-type reactions, selective (partial) and total oxidation reactions, and enzymatic type reactions The book also touches heavily on the biomass applications of metal oxide catalysts and environmentally related/depollution reactions such as COVs elimination, DeNOx, and DeSOx. Finally, the bookiAalso deals with future trends and prospects in metal oxide-based heterogeneous catalysis.